Respuesta :
Note: Since you missed to mention the equations. So, I am taking sample equations (Equation 1 and Equation 2) to make you understand the concept anyways. So, I am answering your question based on the sample questions I will take.
Step-by-step explanation:
Let suppose the equation [1] be
[tex]2x + 4y = 2[/tex]....[1]
Let suppose the equation [2] be
[tex]-x + 3y = 5[/tex]....[2]
Malia Multiplying [tex]-x + 3y = 5[/tex] by 2 so that the x terms will sum to 0 when the equations are combined.
[tex]-2x + 6y = 10[/tex]
Therefore, the equation [2] after multiplication will become [tex]-2x + 6y = 10[/tex].
Adding/combining the new equation after multiplication i.e. [tex]-2x + 6y = 10[/tex] with the equation [1].
[tex]2x + 4y = 2[/tex]
[tex]-2x + 6y = 10[/tex]
_________________
[tex]0+10y=12[/tex]
[tex]10y=12[/tex]
[tex]y=\frac{12}{10}[/tex]
[tex]y=\frac{6}{5}[/tex]
Keywords: system of linear equations
Learn more system of linear equations from brainly.com/question/11690869
#learnwithBrainly